Prognostic Value of Hemoglobin, Albumin, Lymphocyte, and Platelet Score in Locally Advanced Nasopharyngeal Carcinoma - JunMei Song; Lan Luo; Ting Liu; YuQing Lv; Qiulin Huang; Rensheng Wang; Jun Bie (Cancer Medicine, 2026)
ABSTRACT Objective To investigate the prognostic value of the hemoglobin, albumin, lymphocyte, and platelet (HALP) score in patients with locally advanced nasopharyngeal carcinoma (LANPC) receiving concurrent chemoradiotherapy (CCRT), and to clarify its predictive significance for overall survival (OS), progression‐free survival (PFS), locoregional failure‐free survival (LRFFS), and distant metastasis‐free survival (DMFS). Methods Clinical data of 295 patients with LANPC who received CCRT between April 2021 and April 2022 were retrospectively analyzed. Routine blood and biochemical indices were collected within 1 week before CCRT. The HALP score was calculated as follows: HALP = [hemoglobin (g/L) × albumin (g/L) × lymphocytes (10 9 /L)]/platelets (10 9 /L). Patients were divided into high and low HALP groups with the median as the cutoff point. Kaplan–Meier analysis was used to draw survival curves. The log‐rank test was used to compare the survival differences between the high and low HALP groups. Univariate and multivariate Cox regression models were applied to identify independent prognostic factors for patients with LANPC. Results Survival analysis showed that the 3‐year OS of the high and low HALP groups were 95.27% and 93.20%, the 3‐year PFS were 87.84% and 74.15%, and the 3‐year DMFS were 87.84% and 78.91%, respectively. The differences between the groups were statistically significant ( p < 0.05). While the 3‐year LRFFS were 97.30% vs. 96.60%, there were no statistically significant differences between the groups. Multivariate Cox regression analysis confirmed that a low HALP score was an independent risk factor for OS and PFS. Conclusion The HALP group is an effective predictor of prognosis in patients with LANPC. A low HALP group indicated higher disease progression and death. This measurement can be used for prognostic stratification and individualized treatment decision‐making, both simply and economically, and provides a reference for clinical decision‐making and individualized treatment.